From urban to suburban criminology: Understanding crime in America’s "safe" cities - Rocque, Michael (Crime, law and social change, 2017)
Simon Singer’s [1] America’s Safest City represents a new and innovative contribution to the criminological literature. It not only provides a fresh look at understanding crime in America, it sheds the light on a heretofore understudied part of the country, but one that is increasingly populated: Suburbia. Singer offers a new theoretical perspective which he calls "relational modernity." Because the perspective is so new, it is important to critically appraise and evaluate its merits. Thus, this special issue offers an overview and analysis of the book from four luminaries in criminology.